2022
DOI: 10.3390/ijerph19159648
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Novel Bladder Cancer Diagnostic and Surveillance Biomarkers—What Should a Urologist Really Know?

Abstract: The aim of this review is to analyze and describe the current landscape of bladder cancer diagnostic and surveillance biomarkers. We researched the literature from 2016 to November 2021 to find the most promising new molecules and divided them into seven different subgroups based on their function and location in the cell. Although cystoscopy and cytology are still the gold standard for diagnosis and surveillance when it comes to bladder cancer (BCa), their cost is quite a burden for national health systems wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 156 publications
0
10
0
Order By: Relevance
“…Therefore, the diagnostic performances in terms of specificity and sensitivity reported here are generally hard to compare to those previously reported by other authors. Few reviews selecting markers and panels with high diagnostic precision summarized sensitivities and specificities and reported studies yielding sensitivities > 60% at 95% specificity [6,7,10,11,13,37,38]. However, none of these studies investigated as many cases and/or controls as we investigated; thus, it is not clear whether the same sensitivities would have been reported in larger collectives.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, the diagnostic performances in terms of specificity and sensitivity reported here are generally hard to compare to those previously reported by other authors. Few reviews selecting markers and panels with high diagnostic precision summarized sensitivities and specificities and reported studies yielding sensitivities > 60% at 95% specificity [6,7,10,11,13,37,38]. However, none of these studies investigated as many cases and/or controls as we investigated; thus, it is not clear whether the same sensitivities would have been reported in larger collectives.…”
Section: Resultsmentioning
confidence: 93%
“…Due to the direct contact of urine and urothelium, urothelial cancer cells or cancer cell components are released into the urine. Numerous approaches have been carried out to identify UCa by the use of urinary molecular biomarkers [5][6][7][8][9][10][11]. However, none of the used approaches or identified biomarkers have been included in a clinical routine or even in guidelines, possibly due to the complex nature of molecular signatures that, in part, require a specialized readout software [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Multiplex assays that evaluate a composite molecular signature in urine have greater utility in detecting and monitoring BC than efforts to identify a single BC biomarker [ 6 , 7 , 10 , 11 ]. Advantages of multiplex immunoassays include increased efficiency and lower costs versus evaluating multiple analytes individually, and high-throughput capabilities that are further enhanced by using the automated features of modern instrumentation platforms [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further development of urinary biomarkers could have significant benefits since decreasing cystoscopy discomfort has been shown to be a research priority, as demonstrated by the Bladder Cancer Advocacy Network: Patient Survey Network [26]. It is important that novel biomarkers can demonstrate a high negative predictive value to be sufficiently useful to avoid cystoscopy, which has a negative predictive value of 95% [27]. There are currently urinary biomarker tests approved by the US Food and Drug Administration; however, due to low specificity and sensitivity, they have limited use in a clinical setting [28].…”
Section: Low-risk Non-muscle Invasive Bladder Cancermentioning
confidence: 99%